Structural alterations in liver endothelium of rats with dexamethasone-induced insulin resistance - Mohd Shukri, Norfarhana; Muhamad Mukhtar, Shahida; Mohamad, Mashani (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
Liver sinusoidal endothelial cells (LSECs) are perforated with transcellular fenestrations that provide unimpeded access of substrates between sinusoidal blood and hepatocytes. Defenestration refers to the loss of fenestration number and/or decreasing in fenestration diameter which can alter metabolic homeostasis. Insulin resistance has been reported to promote fat accumulation in the liver leading to fatty liver disease. However, the effect of insulin resistance specifically on fenestrations is yet to be investigated. This study was conducted to observe changes in fenestrations of LSEC in response to insulin resistance. Adult male Sprague-Dawley rats were divided into two groups (n=8) where the control group received 0.9% NaCl and the treatment group received dexamethasone injection (1mg/kg) i.p once daily for ten days. At day 11, all rats were anaesthetised using ketamine/xylazine followed by cardiac puncture. Rats were dissected and livers were perfusion-fixed for electron microscopy. Fenestrations were examined using a Quanta FEG450 Scanning electron microscope at 15000x magnification. Ten random images per sample were taken for fenestrations diameter and porosity analysis using ImageJ software. Data was analysed using SPSS version 23.0. Results showed that dexamethasone has induced insulin resistance by a significant reduction of body weight (D=276.84 ±7.87 vs C=393.84±12.47g; p=0.00), increased fasting blood glucose (D=5.57 ±1.30 vs C=3.97±0.55mg/dl; p=0.02) and higher HOMA-IR value (D=1.37±0.52 vs C=0.85±0.22; p=0.00) in treatment group compared to the control. Analysis of the liver images has shown that insulin resistance causes defenestration of LSEC where there is a significant decrease in fenestration frequency (D=3.202±1.16 vs C=2.656±1.044; p=0.04) and endothelial porosity (D=2.17±0.74 vs C=1.77±0.9; p=0.049) but not fenestration diameter. In conclusion, this finding shows that insulin resistance can affect the integrity of liver endothelium specifically on fenestration frequency and liver porosity which will consequently lead to serious implications on liver function as the main site for metabolism.